К вопросу оценки криптографических свойств подстановок случайного типа - Долгов, В. И.; Лисицкая, И. В.; Сергиенко, Р. В.; Обухов, А. Е. (ХНУРЭ, 2008)
The given work is devoted to comparative evaluation of two Sblock selection methods for symmetric block ciphers. The first one is based on the evaluation resistance component of Boolean functions, and the second one uses the criteria of substitution selection, based on the theory of probabilities (for number of the inversion, the increases and the cycles). It is shown, that the quality of the substitution selection according the theory of probabilities do not concede the quality of choose according instrument of Boolean functions in practice.
Keywords: подстановка случайного типа; оценка криптографических свойств